AYURVEDIC VIEW KSHEENA SHUKRA (OLIGOZOOSPERMIA) -MALE INFERTILITY AND ITS MANAGEMENT - Dr. Sanjay A. Dhurve1,Dr. Madhavi P. Mahajan2Dr. Umesh Ghate3, Dr. Ravindra P. Patwardhan4, Dr.Advait Menon 5, Dr. Kirti Bhati6 (Chelonian Research Foundation, 2023)
Male infertility can be defined as an inability to induce conception, due to defect in spermatic functions. The male carrying pathology in semen production includes low sperm count, volume, motility, abnormal forms and sperm functional which impairs the normalcy of the semen and is considered as the main reason for the infertility. Ayurvedic treatment includes medicines, herbal aphrodisiacs, lifestyle changes, dietary changes, psychological therapy, and Panchakarma (detoxification) treatment procedures. Ayurveda give emphasis to the treatment of shukradushti with dhatuvriddhkara, balakara, Shukrajanaka and Shukrapravartaka those in-terms of increasing the sperm count and motility by using vajeekaranadravya. KEY WORDS: -KsheenaShukra,KshinaRetasa, AlpaRetasa, Shukra dosha,